Dynamic comunication mechanism of a distributed DSS: the information retrieval process of the router agent - Stegmayer, Georgina (2000)
We have developed a distributed DSS able to work in a dynamic way. This system is based on the use of mobile agents, which receive the user's queries and visit the DSS domains gathering the required information. One of the main elements to the efficient operation of this system is the router agent. Its responsibility is to give an adequate route to the mobile agents. In this paper we propose a structure for the router agent. It includes a Knowledge Base where the information managed by each domain is represented, and a mechanism of matching the query contents to the domain contents. We also present an interactive strategy to obtain the initial data to be stored in the Router Knowledge Base. The AHP method is used to support the task of evaluating the relative importance among terms representing each domain.